Architectonics Matter: Some Advantages of Treating the Unicity of God in Advance of the Trinity of Persons, in Dialogue with Thomas Aquinas. (April 2017) - Holmes, Christopher R.J.
Abstract: Aquinas's distinction between what is essential and personal in God has been widely criticized in Protestant and Catholic modernity because of its supposed isolation of God from the economy of salvation. Based upon consideration of the divine goodness, I defend Aquinas's arrangement in Summa Theologiae I, qq. 1–49, advancing metaphysical inquiry along four lines. I discuss, first, the fittingness of ascribing conceptual priority to the common in advance of the particular; second, how Aquinas's 'double perspective' illuminates the New Testament language of 'participation' in the divine nature; third, the manner in which God's attributes structure God's works, illustrating the concordance of nature and works; fourth, and last, how Aquinas's architectonic clarifies the relationship between God's essential names and transcendentality.